IDENTIFICATION OF LOCAL WISDOM AND ITS RELATION WITH SCIENCE IN THE CONSTRUCTION OF A RUMAH GADANG IN ISTANO BASA PAGARUYUNG, BATU SANGKAR, WEST SUMATERA - Akmal Yusar (Pendidikan IPA, FMIPA, UNP, 2022)
Rumah Gadang is one of several traditional houses in Indonesia, precisely located in West Sumatra. Rumah Gadang is a residence for the Minangkabau tribe, which at present is almost extinct and has been replaced by modern houses that exist in this era while the remaining is used as a historical museum site of the Rumah Gadang and the function functions of each room that can be visited in certain areas. like Istano Basa Pagaruyuang, Batusangkar. In order for the knowledge of Rumah Gadang to be maintained until generations, there must be an effort to inherit architectural knowledge from the Rumah Gadang, both from the process of making the first milestone or commonly called the Tuo Milestone until later the end of the making of the Rumah Gadang. This paper aims to describe the process of building a Rumah Gadang so that its preservation can be maintained and to show the relationship between the architecture of Rumah Gadang and Science, so that it is related to the culture of Rumah Gadang and the existing science. And also its relation with other sciences such as social science for example in giving